Multi-level switching in TiOxFy film with nanoparticles. (30th August 2017) - Sun, Xiangyu; Wu, Chuangui; Shuai, Yao; Pan, Xinqiang; Luo, Wenbo; You, Tiangui; Du, Nan; Schmidt, Heidemarie
Abstract: A reliable bipolar resistive switching device was achieved with multi-level switching behavior in fluorine-doped titanium oxide (TiO x F y ) film. Different resistance states can be precisely controlled by different pulse voltages, which reveals the device's high potential in neuromorphic research. The characteristics of I – V curves in each resistance state were analyzed. Nanoparticles were observed in the TiO x F y film by HR-TEM. The underlying physical mechanisms during resistance switching are discussed and a model of a meshy conducting path is proposed.